THE IMPACTS OF BULLYING EXPERIENCED BY DAELYN RICE IN THE NOVEL “BY THE TIME YOU READ THIS I’LL BE DEAD” - Salsabila, Putri Aghitstha (Journal of Language and Literature, 2019)
This research is about the impacts of bullying in Julie Anne Peters’s novel entitled By The Time You Read This I’ll be Dead. The purposes of this research are to identify the kinds of bullying and investigate the impacts of bullying experienced by the main character, Daelyn Rice. Researcher used qualitative methods. Researcher used two data sources: primary and secondary. Primary data is By The Time You Read This I’ll be Dead novel by Julie Anne Peters. The sources of secondary data are taken from other sources related the research, such as website, dictionary, and some books which support this research. The results of this research show: 1) Daelyn Rice has three kinds of bullying experienced, that are: Physical bullying, Verbal bullying, and Psychological or Social bullying. 2) Daelyn Rice has four impacts of bullying experienced, that are: Academic impact, Social impact, Psychological impact and Physical impact.